Flamenco deep song - Mitchell, Timothy (Timothy J.) (Yale University Press, 1994)
The dramatic and erotic folk-musical style known as flamenco arose among the stigmatized outgroups of Andalusia - fugitive Jews, Moors, gitanos, blind beggars, harlots, and others - but was quickly embraced and canonized as a fine art by Spanish aristocrats. This lively, highly readable book by Timothy Mitchell is the first full-length investigation of flamenco as well as an absorbing introduction to the cultural psychology of Spain itself. With an arsenal of critical theories honed to a sharp polemical edge, the author targets racialist and politicized mystifications of flamenco and deflates the still-influential primitivism of de Falla and Lorca.